Effect of Rodenticides on Seed Yield of Rabi Crops in Arid Zone - Singh, Bhagwan; Tripathi, R S (Annals of Arid Zone, 2018)
The study was conducted in Bheenjwadia village of Osian Panchyat Samiti of Jodhpur district to disseminate the rodent management technology through demonstrations, trainings, group discussions, field day etc. Rodent control success (mean of 4 years) with single treatment of zinc phosphide (2%) was 68.53, 61.01 and 65.80% in mustard, wheat and cumin crops on 4th day after treatment. Rodent control success (mean of 4 years) with zinc phosphide bait (2% in bajra grain + 2% groundnut oil) followed by bromadiolone (0.005%) was the 70.89-72.87% on 4 DAT which increased further to 79.17-80.74% on 15 DAT. The seed yield of mustard, wheat and cumin increased by 4.9, 7.6 and 9.2% by using rodenticides. The net returns due to adoption of rodenticide baiting technology was of Rs. 2416.78, 3125.50 and 3500.00 ha-1 in mustard, wheat and cumin, respectively as compared to control. Knowledge about the technology was also increased by 44.3% after conducting training program. Key words: Rodent management, dissemination, rabi crops